Spatial heterogeneity in water velocity drives leaf litter dynamics in streams. (5th December 2019) - Bastias, Elliot; Bolivar, Manel; Ribot, Miquel; Peipoch, Marc; Thomas, Steven A.; Sabater, Francesc; Martí, Eugènia
Abstract: Stream hydro‐morphology refers to the heterogeneous distribution of hydrologic conditions that occur above a complex benthic surface such as a streambed. We hypothesised that hydro‐morphological conditions will influence the retention, re‐distribution, and microbial‐driven decomposition of leaf litter inputs in stream ecosystems because each process varies with overlying water velocity. We tested this hypothesis using: (1) the spatial distribution of water velocity within a stream reach as a surrogate of stream hydro‐morphology; (2) leaf tracer (i.e. Ginkgo biloba L.) additions with serial recovery to examine the relationship between benthic retention and overlying velocity; and (3) measurements of leaf litter decomposition (i.e. Alnus glutinosa [L.] Gaertn.) under different water velocity conditions. Results demonstrate that water velocity exerts a significant influence on the retention and re‐distribution of leaf litter inputs within the reach. The observed range of water velocity (from c. 0 to 0.92 cm/s) also strongly influences the range of leaf litter decomposition rates (0.0076–0.0222/day). Our findings illustrate that water velocity influences leaf litter dynamics in streams by controlling leaf litter transport, retention and re‐distribution as well as how leaves decompose within recipient stream reaches. Ultimately, the results show that the efficiency of leaf litter inputs in supporting stream ecosystem function is dependent on the hydro‐morphological characteristics of the receiving stream ecosystems.